Ethosuximide‐induced drug reaction with eosinophilia and systemic symptoms with mediastinal lymphadenopathy. Issue 4 (27th May 2019) - Werbel, Tyler; Castrovinci, Philip; Contestable, James
Abstract: Lymphadenopathy is a common sign for drug reaction and eosinophilia with systemic symptoms (DRESS) syndrome, but hilar and mediastinal lymphadenopathy may be underreported. We describe a 7‐year‐old boy who started taking ethosuximide for absence seizures and presented with diffuse rash, fever, elevated transaminases, facial swelling, and hilar and mediastinal lymphadenopathy. His mediastinal lymphadenopathy was concerning for lymphoma, which led to more invasive testing to rule out malignancy. This report highlights an unusual and likely underreported presenting sign of DRESS syndrome in children.